KOt-Bu-promoted selective ring-opening N-alkylation of 2-oxazolines to access 2-aminoethyl acetates and N-substituted thiazolidinones - Lin, Qiao; Zhang, Shiling; Li, Bin (Beilstein Journal of Organic Chemistry, 2020)
An efficient and simple KOt-Bu-promoted selective ring-opening N-alkylation of 2-methyl-2-oxazoline or 2-(methylthio)-4,5-dihydrothiazole with benzyl halides under basic conditions is described for the first time. The method provides a convenient and practical pathway for the synthesis of versatile 2-aminoethyl acetates and N-substituted thiazolidinones with good functional group tolerance and selectivity. KOt-Bu not only plays an important role to promote this ring-opening N-alkylation, but also acts as an oxygen donor.
Keywords: N-alkylation; oxazolines; potassium tert-butoxide; ring opening; thiazolidinones

(untitled) - Arockiam, P. B.; Bruneau, C.; Dixneuf, P. H. (Chem. Rev., 2012)

(untitled) - Weng, Y.; Lv, W.; Yu, J.; Ge, B.; Cheng, G. (Org. Lett., 2018)

(untitled) - Luo, B.; Weng, Z. (Chem. Commun., 2018)

(untitled) - Johnson, J. S.; Evans, D. A. (Acc. Chem. Res., 2000)

(untitled) - Gómez, M.; Muller, G.; Rocamora, M. (Coord. Chem. Rev., 1999)

(untitled) - Gant, T. G.; Meyers, A. I. (Tetrahedron, 1994)

(untitled) - Magano, J. (Chem. Rev., 2009)

(untitled) - de la Rosa, V. R.; Tempelaar, S.; Dubois, P.; Hoogenboom, R.; Mespouille, L. (Polym. Chem., 2016)

(untitled) - Qiao, K.; Yuan, X.; Wan, L.; Zheng, M.-W.; Zhang, D.; Fan, B.-B.; Di, Z.-C.; Fang, Z.; Guo, K. (Green Chem., 2017)

(untitled) - Gutmann, B.; Roduit, J.-P.; Roberge, D.; Kappe, C. O. (Chem. – Eur. J., 2011)

(untitled) - Laitar, D. S.; Kramer, J. W.; Whiting, B. T.; Lobkovsky, E. B.; Coates, G. W. (Chem. Commun., 2009)

(untitled) - Singh, S. P.; Parmar, S. S.; Raman, K.; Stenberg, V. I. (Chem. Rev., 1981)

(untitled) - Williamson, A. E.; Ylioja, P. M.; Robertson, M. N.; Antonova-Koch, Y.; Avery, V.; Baell, J. B.; Batchu, H.; Batra, S.; Burrows, J. N.; Bhattacharyya, S.; Calderon, F.; Charman, S. A.; et al. (ACS Cent. Sci., 2016)

(untitled) - Cai, L.; Qu, B.; Hurtle, B. T.; Dadiboyena, S.; Diaz-Arrastia, R.; Pike, V. W. (ACS Chem. Neurosci., 2016)

(untitled) - Przeslak, A. D.; Inman, M.; Lewis, W.; Moody, C. J. (J. Org. Chem., 2018)

(untitled) - Singh, B.; Pennock, P. O.; Lesher, G. Y.; Bacon, E. R.; Page, D. F. (Heterocycles, 1993)

(untitled) - Mahy, W.; Plucinski, P.; Jover, J.; Frost, C. G. (Angew. Chem., Int. Ed., 2015)

(untitled) - Ouyang, L.; Qi, C.; He, H.; Peng, Y.; Xiong, W.; Ren, Y.; Jiang, H. (J. Org. Chem., 2016)

(untitled) - Nocera, G.; Young, A.; Palumbo, F.; Emery, K. J.; Coulthard, G.; McGuire, T.; Tuttle, T.; Murphy, J. A. (J. Am. Chem. Soc., 2018)

(untitled) - Barham, J. P.; Coulthard, G.; Emery, K. J.; Doni, E.; Cumine, F.; Nocera, G.; John, M. P.; Berlouis, L. E. A.; McGuire, T.; Tuttle, T.; Murphy, J. A. (J. Am. Chem. Soc., 2016)

(untitled) - Rehan, M.; Maity, S.; Morya, L. K.; Pal, K.; Ghorai, P. (Angew. Chem., Int. Ed., 2016)

(untitled) - Pichette Drapeau, M.; Fabre, I.; Grimaud, L.; Ciofini, I.; Ollevier, T.; Taillefer, M. (Angew. Chem., Int. Ed., 2015)

(untitled) - Feng, J.-B.; Wu, X.-F. (Adv. Synth. Catal., 2016)

(untitled) - Wang, H.; Ying, J.; Lai, M.; Qi, X.; Peng, J.-B.; Wu, X.-F. (Adv. Synth. Catal., 2018)

(untitled) - Liu, S.; Zhang, S.; Lin, Q.; Huang, Y.; Li, B. (Org. Lett., 2019)

(untitled) - Midya, G. C.; Kapat, A.; Maiti, S.; Dash, J. (J. Org. Chem., 2015)

(untitled) - Hünig, S. (Angew. Chem., Int. Ed. Engl., 1964)

(untitled) - Fenster, E.; Smith, B. T.; Gracias, V.; Milligan, G. L.; Aubé, J. (J. Org. Chem., 2008)